Dynamic adsorption of cetyl trimethyl ammonium bromide at decane/water interface - Salamah, A.; Phan, Chi; Pham, H. (Elsevier B.V., 2015)
The dynamic adsorption of cetyl trimethyl ammonium bromide (CTAB) was investigated at decane/waterinterface by pendant drop technique. The images were analysed using Axisymmetric Drop Shape Analysissoftware and then were modelled using a new model. The model provided a unique solution for equilib-rium adsorption. Consequently, dynamic data at two different concentrations were fitted simultaneouslyto determine the adsorption parameters. Good fittings have been achieved and then applied to predictdynamic tension at other concentrations. The outcomes revealed a significant increment in term of inter-facial adsorption in comparison with adsorption at the air/water interface. The nature of this increment can be explained by considering the impacts of hydrophobic oil molecules and interfacial layer arrange-ments of alkane/water interfaces. The results can be used to quantify the interaction between alkane and the hydrocarbon tail of ionic surfactants at the oil/water interface.